Desires and Affects in Organizations: Spinoza’s Contributions to a Critical Study - Soares Siqueira, Marcus Vinicius; Dias, Cledinaldo Aparecido (Organizações & Sociedade, 2025)
By contemplating the philosophical complexity of affects and desire as power, this theoretical essay aims to critically discuss the dynamics of desire and affects in contemporary organizations, with Spinoza as the main theoretical inspiration. The study is characterized as theoretical-critical and counter-hegemonic, supporting a process of socio-organizational transformation as it resists the homogenizing, totalitarian discourse of reification and instrumentalization; denouncing ways of capturing and kidnapping subjectivities. Reflecting on this implies uncovering aspects that conceal strategies of domination and instrumentalization of the subject through the development of people management policies and practices, which usurp the power emanating from the worker’s desire and manage affects according to their own interests. In this dynamic, organizations seek to achieve the enthusiastic adherence of employees, who invest all their innovative, creative and affectionate potential in the hope of obtaining positive affects that can give meaning to their existence. And Spinoza, in his reflections developed at both an ontological and political level, becomes a rich source for thinking about the individual-company relationship, especially when we start from his positions on freedom, servitude, valuing multiplicity, perseverance in existence and the power to act.